ANALISA PROSES BISNIS SISTEM ERP (ENTERPRISE RESOURCE PLANNING) PADA PERUSAHAAN DISTRIBUTOR BATU BARA: ANALISIS OF ERP (ENTERPRISE RESOURCE PLANNING) SYSTEM IN COAL DISTRIBUTOR COMPANIES - Nadziroh, Faridatun (Jurnal Teknologi dan Terapan Bisnis, 2019)
The strategies of procurement business process had to be innovative, effective, and efficient in order for the company can still competitive in the business world. One of the strategies used with ERP systems is now implemented as one solution based on products or services. This research using qualitative methodology, where the data received and processed in the form of data depiction of field conditions the research, not a number or calculation but the data processed by analyzing results of interviews and documents provided by the company. By using an ERP system, companies can be helped by integrating all business transactions within the company. In addition, users also have an important role in the ERP system, because users have a direct involvement in the influence of cultural changes after the system implementation is executed. The implementation of the ERP system in this study was applied to one of the coal distributor companies. The results of the research analysis show that the existence of an ERP system in business processes can help the user in completing work more easily and quickly, because the data that the user enters into the system will be formed into information. And the ERP system in the company results in changes in work culture that are usually done manually and some are done orally must be done documented both on the system and in an archive